Adsorption of textile wastewater on alkali-activated sand. (20th May 2019) - Sharma, Aditya; Syed, Zainab; Brighu, Urmila; Gupta, Akhilendra Bhushan; Ram, Chhatra
Abstract: This paper deals with the removal of residual dyes from actual textile wastewater after receiving coagulation-flocculation treatment by employing alkali-activated local sand as a novel low-cost adsorbent. The activation process was found to increase the surface area and negative charge on the sand surface thereby offering good adsorption capacity. Batch adsorption studies were carried out with respect to contact time (3–30 min) and amount of adsorbent (12.5–100 g) to evaluate its dye removal capacity from wastewater. The surface of natural, modified and dye adsorbed sand was characterized using X-ray Diffraction analysis (XRD), Scanning Electron Microscopy (SEM), Zeta Potential Analysis and Fourier Transform Infrared Spectroscopy (FTIR) to understand the mechanism of sorption. To examine the adsorption behavior Lagergren's pseudo-first order, second order, and intraparticle diffusion models were applied for kinetic studies. These studies indicated that pseudo-second order model fitted the best; yielding a high correlation coefficient ( R 2 ) of more than 0.995. The color removal using modified sand was found to be 70% in first 3 min while non-modified sand could only remove 40% of dye molecules, even after 20 min of adsorption. The results suggest that the activated sand can be used as a cost-effective adsorbent for color removal from wastewater of textile industries. Graphical abstract: Image 1 Highlights: Characterization of the non-modified and alkali modified sand surface. Color removal increased by 30% due to alkali-activation of sand particles. Quick removal within 3 min was observed on using activated sand as adsorbent. Semi-receptive nature of the activated sand particles towards selective dyes governed the removal. Lagergren's pseudo-second order model fitted best with the adsorption data.